1997
DOI: 10.2337/diab.46.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Human Insulin With Palmitic Acid Extends the Time Action of Human Insulin in Diabetic Dogs

Abstract: To test whether the binding of insulin to an endogenous serum protein can be used to extend the time action of insulin, human insulin was acylated at the epsilon-amino group of Lys(B29) with palmitic acid to promote binding to serum albumin. Size-exclusion chromatography was used to demonstrate specific binding of the resulting analog, [N(epsilon)-palmitoyl Lys(B29)] human insulin, to serum albumin in vitro, and the time action and activity of the analog were determined in vivo using overnight-fasted, insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…GLP-1 that is not degraded by DPP IV is rapidly cleared from the circulation by renal filtration (Hassan et al, 1999). It has been found that insulin can be renally retained by binding to serum albumin through derivatisation with fatty acids (Kurtzhals et al, 1995;Markussen et al, 1996;Myers et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLP-1 that is not degraded by DPP IV is rapidly cleared from the circulation by renal filtration (Hassan et al, 1999). It has been found that insulin can be renally retained by binding to serum albumin through derivatisation with fatty acids (Kurtzhals et al, 1995;Markussen et al, 1996;Myers et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Spectra were recorded using a quadripole ion trap mass analyser and collected using full ion scan mode over the m/z range 150-2000. Covalent attachment of fatty acids to peptides has been explored as a potential tool to deliver soluble therapeutic agents with protracted modes of action (Hashimoto et al, 1989;Kurtzhals et al, 1995;Markussen et al, 1996;Myers et al, 1997). tration may only be as long as 3 to 4 min (Deacon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the NH 2 -terminus can adopt many different conformations with certain ones having high affinity for the PAC1-R, our approach was to systematically explore the initial 5 residues of PACAP using substitutions that resulted in conformationally-restricted analogs. We also explored the results of selective substitutions in other sites that might conformationally-restrict the PACAP-analog, which could affect degradation or could extend its half-life in the circulation, such as the attachment of long-chain fatty-acids[7,21,39]. The latter approach was included because PACAP38 has a plasma half-life of <5–10 minutes[4,4,7,31], which restricts its therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our results show that the attachment of a fatty-acid on the COOH-terminus lysine [Lys(palmitoyl) 38 ] (P12, P13 and P14) had only a minimal effect on PAC1-affinity and thus could be an important substitution for PAC1-R selective agonists in the future. One of the main problems with the potential therapeutic use of PACAP is its short half-life[4,31]; however, recent studies with other peptides (insulin, glucagon,glucagon-like peptide 1) show that e attachment of long-chain fatty acids greatly extends their half-lives[21,39,56]. …”
Section: Discussionmentioning
confidence: 99%